Implementasi Kurikulum Pendidikan Agama Islam (PAI) dalam Meningkatkan Akhlak Siswa SD - Ubaidillah, Moh Faiz; Hasan, Zainul; Izzat (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Islamic Religious Education (PAI) has an important role in shaping students' morals, especially at the elementary school (SD) level. The PAI curriculum is expected to provide a strong foundation for the formation of students' character and morals through teaching Islamic religious values. This article aims to examine the implementation of the PAI curriculum in elementary schools and how this curriculum can improve student morals. This research shows that the PAI curriculum applied with the right approach can increase students' understanding of Islamic teachings and shape their behavior in accordance with religious values, such as honesty, discipline and respect for others. However, effective implementation requires support from competent teaching staff, relevant teaching materials, and collaboration between schools and parents